FACTORS INFLUENCING COMPLIANCE TO THERAPEUTIC REGIMEN AMONG PATIENTS WITH HYPERTENSION - Dharan, Dhanya R; Kt, Moly (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The objectives of the study were to identify the level of compliance to therapeutic regimen, assess the factors promoting and interfering compliance, and to find the association between level of compliance and factors influencing it in patients with hypertension in a Tertiary Care Hospital, Kochi, with a view to develop an information booklet. Methods: Nonprobability convenience sampling technique was used to collect data from 150 individuals attending outpatient departments. Data on compliance were assessed through interview using standardized Hill And Bone High Blood Pressure Compliance. Scale and factors promoting and interfering compliance were assessed using self-developed semi-structured questionnaire. Results: Only 55 (36.7%) had good compliance, while 52 (34.7%) had average and 43 (28.7%) had poor compliance to anti-hypertensive therapeutic regimen. The major factors promoting compliance were found as patient-prescriber relationship 146 (97.3%), family support 133 (88.7%), motivation 125 (83.3%), communication with healthcare providers 122 (81.3%), health literacy 104 (69.3%), and patient satisfaction 75 (50%). The factors interfering with compliance were lack of self-esteem 136 (90.7%), long-term adherence 129 (86%), misconceptions and erroneous beliefs 122 (81.3%), cost of therapy and income 100 (80%), forgetfulness 107 (71.3%), difficulty in adjustment to dietary change 82 (54.7%), and fear of side effects 70 (50%). A significant association between the level of compliance and factors promoting and interfering with compliance to therapeutic regimen (p<0.01) was noted. Level of compliance with therapeutic regimen was found to be lower in patients with associated comorbidities such as diabetes mellitus (c2=9.52, p<0.01) and coronary artery disease (c2=6.737, p<0.05). Conclusion: The study concludes the significance of developing systems to tack and ensure compliance to therapy among hypertensives with a focus on factors promoting compliance not only from the patient perspective but also from the perspective of family and society.